Modulating the methanation activity of Ni by the crystal phase of TiO2. Issue 13 (5th June 2017) - Lin, Yaping; Zhu, Yifeng; Pan, Xiulian; Bao, Xinhe
Abstract : The methanation activity of Ni is significantly enhanced by using rutile TiO2 as the support with respect to anatase. Abstract : We demonstrate that the methanation activity of Ni catalysts is modulated by the crystal phase of the TiO2 support. The rutile TiO2 (r-TiO2 )-supported Ni catalyst gives a turnover frequency almost two orders of magnitude higher than the anatase TiO2 (a-TiO2 )-supported catalyst although the two catalysts exhibit a similar mean Ni particle size. Characterization by H2 -TPR, H2 -TPD, XPS and IR reveals a stronger interaction between Ni and r-TiO2, leading to a higher capability of CO activation and hydrogenation activity of Ni although Ni is partially covered by TiO x overlayers during reaction. Interestingly, the modulating effects of the titania crystal phases are much more pronounced on the activity of Ni in CO2 methanation.